Why the NPV Criterion does not Maximize NPV - Berkovitch, Elazar; Israel, Ronen (Review of Financial Studies, 2004)
This article presents a theory of capital allocation that shows how the use of net present value (NPV) as an investment criterion leads to inefficient capital budgeting outcomes and how this criterion may be dominated by other capital budgeting criteria, like the internal rate of return and the profitability index. The essence of our theory is rooted in the mainstream paradigm of corporate finance: while firms use NPV to measure the addition to firm value from prospective projects, "classical" informational and agency considerations prevent it from implementing the optimal capital budgeting outcome. Our theory also identifies conditions when alternative criteria should be used. Finally, we characterize when direct monitoring through capital budgeting dominates compensation contracts in alleviating the agency problem. Copyright 2004, Oxford University Press.